2020
DOI: 10.3390/nu12020343
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine Disruptor Bisphenol A (BPA) Triggers Systemic Para-Inflammation and is Sufficient to Induce Airway Allergic Sensitization in Mice

Abstract: Allergic airway diseases are accompanied by increased permeability and an inflammatory state of epithelial barriers, which are thought to be susceptible to allergen sensitization. Although exogenous drivers (proteases, allergens) of epithelial barrier disruption and sensitization are well studied, endogenous contributors (diet, xenobiotics, hormones, and metabolism) to allergic sensitization are much less understood. Xenoestrogens are synthetic or natural chemical compounds that have the ability to mimic estro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 63 publications
1
10
0
Order By: Relevance
“…Additionally, this substance promoted the expression of the cytokine TSLP. In vivo, BPA significantly induced systemic inflammation as the levels of inflammatory mediators in the skin, intestines and respiratory system increased [32]. A similar study was conducted in which an exacerbation of allergy to egg proteins was observed as a result of exposure to BPA.…”
Section: Description Of Knowledgementioning
confidence: 73%
“…Additionally, this substance promoted the expression of the cytokine TSLP. In vivo, BPA significantly induced systemic inflammation as the levels of inflammatory mediators in the skin, intestines and respiratory system increased [32]. A similar study was conducted in which an exacerbation of allergy to egg proteins was observed as a result of exposure to BPA.…”
Section: Description Of Knowledgementioning
confidence: 73%
“…Thus they alter gene expression as well as intracellular transduction pathways [79]. After incorporation they can also compete with endogenous hormones and other substances for binding to carrier proteins [80] or metabolization and interfere with epithelial cells triggering systemic para-inflammation [81].…”
Section: Newly Described Mechanisms Of Action For Edcs and Their Poss...mentioning
confidence: 99%
“…2 Recent reports paid the attention towards the findings that chronic exposure to BPA may cause endocrinal dysfunction. 3,4 These findings might be attributed to the close similarity between the phenol groups in both BPA and estradiol, which may confer an effect to BPA on the estrogenic pathways in the body. 5 In addition, high concentrations of BPA were proven to block the androgen receptors (AR), modulate Leydig cell steroidogenesis, and hinder LH receptor-ligand binding.…”
Section: Introductionmentioning
confidence: 99%